Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Answer:
- 1
Step-by-step explanation:
Substitute a = - 1 into the expression, that is
(- 1)³ - 2(- 1)² + 3(- 1) + 5
= - 1 - 2(1) - 3 + 5
= - 1 - 2 - 3 + 5
= - 6 + 5
= - 1
Answer:
=(-1)³-2(-1)²+3(-1)+5
=-1-2(1)+3(-1)+5
=-1-2+3+5
=-3+8
=5
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.